An efficient papaya leaf distortion mosaic potyvirus vector for virus-induced gene silencing in papaya. (1st July 2021) - Tuo, Decai; Yan, Pu; Zhao, Guangyuan; Cui, Hongguang; Zhu, Guopeng; Liu, Yang; Yang, Xiukun; Wang, He; Li, Xiaoying; Shen, Wentao; Zhou, Peng
Abstract: Papaya ( Carica papaya L.) is regarded as an excellent model for genomic studies of tropical trees because of its short generation time and its small genome that has been sequenced. However, functional genomic studies in papaya depend on laborious genetic transformations because no rapid tools exist for this species. Here, we developed a highly efficient virus-induced gene silencing (VIGS) vector for use in papaya by modifying an artificially attenuated infectious clone of papaya leaf distortion mosaic virus (PLDMV; genus: Potyvirus ), PLDMV-E, into a stable Nimble Cloning (NC)-based PLDMV vector, pPLDMV-NC, in Escherichia coli . The target fragments for gene silencing can easily be cloned into pPLDMV-NC without multiple digestion and ligation steps. Using this PLDMV VIGS system, we silenced and characterized five endogenous genes in papaya, including two common VIGS marker genes, namely, phytoene desaturase, Mg-chelatase H subunit, putative GIBBERELLIN (GA)-INSENSITIVE DWARF1A and 1B encoding GA receptors; and the cytochrome P450 gene CYP83B1, which encodes a key enzyme involved in benzylglucosinolate biosynthesis. The results demonstrate that our newly developed PLDMV VIGS vector is a rapid and convenient tool for functional genomic studies in papaya.